KOMPETENSI MENGAJAR DOSEN PTS JAWA TIMUR - Utomo, Dwi Priyo; Rofieq, Ainur (Jurnal Bestari, 1993)
Theoretically, additional education can improve lecturer's competence in teaching. Research, however, concluded that there was not any significant difference between teaching competence and lecturer's level education. The fact above has two possiblities i.e. first, the lecturers who studied in magister program might not be relevant to their educational background (scholar of S1). Second, for those who studied in magister program might have had some teaching experience before. Dwi Priyo Utomo and Ainur Rofieq summerize Endang Purwanti's research entitled